The dilemma of prioritizing: are we ignoring the elderly - Behera, Ashish (International Journal of Advances in Medicine, 2021)
Thie COVID-19 pandemic has brought about a lot of changes in the perspectives towards the aging persons of the community. It has also brought out the flaws of medical care to the table of discussions and the rational utilization of the limited resources available. Through this article, I want to raise the issue of prioritization of young over the old in limited-resource settings, especially in the developing countries